Community Language Learning (CLL) in Tertiary Level: A Learner Friendly Approach to ELT in Bangladesh - Bari, Tazreen Jahan (REiLA : Journal of Research and Innovation in Language, 2020)
This paper entitled "CLL in Tertiary Level: A Learner Friendly Approach to ELT in Bangladesh" aims to analyse the problems faced by tertiary level language learners in Bangladesh. This paper shows how Community Language Learning (CLL) can be a learner-friendly approach that creates an environment and process fit for maximum efficiency in target language learning. This paper analyses the quantitative data collected via questionnaire from fifty tertiary level students of Bangladesh from five universities across Bangladesh. This study reveals that tertiary level students face more barriers in classroom participation due to self-consciousness and anxiety. This study further reveals that using the CLL method that treats learners like a whole person allows them to take responsibility for their learning process. It also promotes small study groups consisting of peers and a counsellor-teacher to provide a more efficient learning environment is friendly to the learners. Thus, this study asserts that CLL is the most learner-friendly and efficient approach to ELT in the tertiary level and opens future research possibilities on how this method can be implemented.